Volatiles or TIVA: Which is the standard of care for pediatric airway procedures? A pro‐con discussion. Issue 3 (27th January 2020) - Lauder, Gillian R.; Thomas, Mark; von Ungern‐Sternberg, Britta S.; Engelhardt, Thomas
Abstract: Anesthesia for pediatric airway procedures constitutes a true art form that requires training and experience. Communication between anesthetist and surgeon to establish procedure goals is essential in determining the most appropriate anesthetic management. But does the mode of anesthesia have an impact? Traditionally, inhalational anesthesia was the most common anesthesia technique used during airway surgery. Introduction of agents used for total intravenous anesthesia (TIVA) such as propofol, short‐acting opioids, midazolam, and dexmedetomidine has driven change in practice. Ongoing debates abound as to the advantages and disadvantages of volatile‐based anesthesia versus TIVA. This pro‐con discussion examines both volatiles and TIVA, from the perspective of effectiveness, safety, cost, and environmental impact, in an endeavor to justify which technique is the best specifically for pediatric airway procedures.